The Implementation of The Extension Management Function to The Success of Empowering Farmer Women's Groups in The Sustainable Food House Area (KRPL) Program - Siti Wahana; Achmad Faqih; Euis Krismayanti; Maria Ulfah; Putri Silvani; Sintia Ratnasari Dewi (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The Women's Farmer Group (KWT) really needs management to process agricultural products to be more developed. In an effort to empower farmers, group processing is needed which is carried out from, by and for farmers. But in this case, the management function of the Harapan peasant women's group Ciputat Village, Ciawigebang District, Kuningan Regency In the aspects of planning, organizing, implementing, supervising and assessing the success of empowerment is still not optimally applied. Therefore, researchers will explore the application of the extension management function to the success of empowering farmer women's groups in Ciputat Village, Ciawigebang District, Kuningan Regency. The study was conducted from July to September 2022. The research design used is descriptive quantitative research. The data collection techniques that researchers use are questionnaires, documents, and interviews. Research data was analyzed using statistics to determine respondents' responses regarding research variables submitted through research instruments in the form of questionnaires. To determine the effect between independent variables, namely the extension management function (X1, X2, X3, and X4) on the success of empowering farmer women groups (Y) Using Descriptive data analysis and regression analysis. The results showed that the strong relationship between the variables of the extension management function (planning, organizing, implementing and supervising) with the success of empowering farmer women's groups was shown by the simultaneous correlation coefficient R of 0.924, this showed a relationship that was classified as 'very high' at 0.60 – 0.80